Intra-frame prediction in H.264/AVC video codec and distributed video compression - Neo, Michelle Li Min (2010)
This project investigates into two video coding paradigms: the start-of-the-art standard and an emerging technology. H.264/AVC is the latest block-oriented motion-compensation-based codec standard to create a standard capable of providing good video quality at substantially lower bit rates than the previous standards such as MPEG-2, H.263 or MPEG-4. Distributed video coding (DVC) is the new paradigm for video compression based on two theorems, namely Slepian-Wolf and Wyner-Ziv information theoretic results from the 1970s. This reduces the complexity during video encoding as the computations are being shifted over to the decoder. Most encoder and decoder use a feedback channel to allocate a proper number of bits to each frame. However, this causes a limitation as feedback channel may not exists in some applications such as offline processing.